Use of clinoptilolite aluminosilicate (ZeoterA) in the cultivation of beans (Phaseolus vulgaris) controlling anthracnose (Colletotrichum lindemuthianum) under different doses of phosphorus - Pazmiño Muñoz, Edison Marcelo; Sánchez Iznaga, Ángel Lázaro; Realpe Iduarte, José Antonio; Baldeon Prieto, Gregorio Justino; Romero Troya, Yomaira Alexandra; Herrera Egüez, Favio Eduardo (Ingeniería Química y Desarrollo, 2024)
The objective of this research was to evaluate the use of clinoptilolite aluminosilicate (ZeoterA) in the bean (Phaseolus vulgaris) crop controlling anthracnose (Colletotrichum lindemuthianum) under different doses of phosphorus. The design used was Completely Random Blocks (DBCA) with six treatments with different doses of ZeoterA. They were divided into two applications of fertilizers and ZeoterA during the trial and different agronomic variables were evaluated. The different agronomic variables were subjected to Analysis of Variance using Tukey's test at 95% probability. The severity of C. lindemuthianum was evaluated by applying visual scales and the Leaf Doctor software. At the end of the test, it was determined that the application of 70 - 15 - 40 kg/ha (N-P-K) + Zeolite (150 kg/ha) has a positive effect on the health of the bean pod and decreases pod rot. This treatment presented the highest yield 2.45 kg/ha and a greater productive response in agronomic variables such as plant height (30.90 cm) and weight of 100 seeds (68 g). This treatment also presented a better Benefit/Cost Ratio of 36% over the control.
Keywords: Colletotrichum lindemuthianum; Zeolite; Phosphorus; Leaf Doctor